Análisis de la normativa aplicable por el derrame de hidrocarburos en Ventanilla - Lazo Oscanoa, Carlos Alberto (2022)
The oil spill off the coast of Ventanilla and other districts, which is responsible for the La Pampilla Refinery, caused a large-scale environmental disaster; OEFA reported affecting an area of 11, 061 ha y 11, 900 barrels of oil. The objective of this research is to analyze from a normative point of view the competences that the various institutions should assume in the case. The research carried out through a qualitative approach is of a descriptive type due to the collection of data and the selection of information from various sources. Regarding the results, with respect to administrative responsibility, for the action of the OEFA, five administrative sanctioning processes have been initiated from the sixteen administrative measures issued. About the criminal liability, the offense of pollution under article 304 of the Criminal Code applies. Regarding environmental responsibility, measures are contemplated for restoration and recovery and the cost of the risks or damages generated. It concludes by specifying the applicable environmental regulations on the procedures to be assumed and on environmental responsibility, the lack of Peruvian regulations was identified.